Field Investigation of Face Spall in Moderate Strength Coal Seam at Vang Danh Coal Mine, Vietnam - Tien Dung, Le; Hong Quang, Dao (VNU Journal of Science: Earth and Environmental Sciences, 2021)
Face spall in moderate strength coal seam occurs less frequently but can be more severe and takes a longer time to remedy compared to face spall in the weak coal seam. This paper presents a field investigation of face spall in moderate strength coal seam at Face I-8-1, Vang Danh coal mine, Quang Ninh coal field, Vietnam. The leg pressure of shield support and face condition were monitored within two months, and on-site remedial measures to the spall were discussed. The monitoring results confirmed that the front and rear leg pressure profiles are consistent with world-wide observations. The coal face condition in actual operation was found to be more stable than that in project design. The face spall occurred along face dip direction, but mostly in small extent of less than 0.5 m deep and during transitional time between working shifts. Proper ground control near gate ends by using higher capacity shield supports and supplemental hydraulic props was identified to improve face stability in the area. On-site remedial measures proved their efficiency in small to moderate face spall extent. For main roof rupture-associated face spall, technical measures have been applied but they need further investigation to clarify their effectiveness. The paper’s results can be consulted to improve longwall face stability control in similar coal seam conditions.